APLIKASI PENYEWAAN MOBIL SAHABAT MAJU BORNEO BERBASIS ANDROID - Ivanka Flowers, Patrick; Darmanto, Tony; Hendro, Hendro (INTEKSIS, 2024)
In the current era of globalization, information technology is rapidly advancing, supporting almost all operations with technology-based applications, including Android smartphones. This technology facilitates access to information and data processing, thereby enhancing the efficiency and productivity of various sectors. Many service businesses now promote themselves through social media and print media, offering wide reach and direct interaction with customers. Service businesses, including car rental services, need to adopt technology to efficiently and effectively meet customer needs. Conventional car rental often faces issues such as vehicle condition discrepancies, complex administrative processes, and difficulties in monitoring orders and customer data. CV. Sahabat Maju Borneo in Kubu Raya Regency, West Kalimantan, also experiences difficulties in monitoring orders, facing customer data uncertainties, and constraints in selecting types of cars and knowing applicable rates. To address these issues, the author has developed a service application. This application allows business owners to monitor orders, view customer data, review rates, and record available car data. Customers can request rentals, choose cars, access rental rules, and know rates through this application. The "Sahabat Maju Borneo" application is effective in addressing various problems faced by conventional car rentals. This digital innovation enhances customer satisfaction and business productivity, and supports business sustainability in the modern technology era. Keywords: Application, Car, Rental, Service Business, Android.